Paths to Making a Difference: Leading In Government - Abramson, Mark A.; Lawrence, Paul R. (Rowman & Littlefield Publishers, 2012)
To understand the challenges of political leadership and how top executives succeed in accomplishing an administration's objectives, business in government experts Paul R. Lawrence and Mark A. Abramson present the findings of a two year's study of top political appointees in the Obama administration. The participants—deputy secretaries and agency heads—provide case studies of how each approaches the management challenges and achieves the mission of their organization. Full of behind-the-scenes insights and practical advice from government political executives on how they face management challenges in real time, Paths to Making a Difference: Leading in Government offers indispensable insights to current and prospective political appointees and everyone interested in understanding how leaders work to make government agencies more effective.